Corrosivity of haze constituents to pure Mg - Chen Zhao; Fuyong Cao; Guang-Ling Song (Journal of Magnesium and Alloys, 2020)
The corrosion behavior of pure Magnesium (Mg) in a Mg(OH)2-saturated solution containing different individual constituents of PM2.5 in haze were studied by hydrogen evolution, weight loss and electrochemical experiments. The results indicated that the corrosivity of these constituents to pure Mg decreased in the following order: (NH4)2SO4>Haze-contaminated-solution>NH4NO3>NH4Cl>NaCl ≈ KCl ≈ Na2SO4 ≈ MgCl2 ≈ CaSO4>Mg(OH)2 (basic solution) >Ca(NO3)2. Possible mechanisms behind the different corrosion behaviors of Mg in response to these constituents were also briefly discussed in this paper. Keywords: Haze (PM2.5), Mg, Corrosion